Practical phosphorylation of polymers: an easy access to fully alcohol soluble synthetically and industrially important polymers - ÇAKMAKÇI, EMRAH (ROYAL SOC CHEMISTRY, 2021)
Phosphorus-containing polymers have always been privileged structures in polymer science due to the widespread use of these polymers in various fields, particularly in bio-related applications. It is therefore of utmost importance to endow synthetic and industrial polymers with phosphorus units not only to enlarge their potential use in bio-related applications, but also to improve the ease of processing and operation simplicity for various applications. In this study, we report a facile method to synthesize polymers with phosphorus pendant groups. A commercial compound, namely bis(diethoxyphosphoryl) acetylene, where a triple bond is bonded to two phosphodiester (PvO(OC2H5)(2)) units was reacted with various azide-functionalized synthetically and industrially important polymers, such as polystyrene (PS), polyester (PE), polyurethane (PU), polycarbonate (PC), polyvinyl chloride (PVC), and polyepichlorohydrin (PECH), in a green solvent, 2-methyltetrahydrofuran (MeTHF), through metal-free azide-alkyne 1,3-dipolar cycloaddition reactions. It was found that all the phosphorylated polymers became soluble in a variety of alcohols due to the contribution of phosphodiester units. Moreover, the thermal properties of the phosphorylated polymers were analyzed and significant enhancements in thermal stabilities were found compared with their phosphorus-free precursors. Since phosphorylation of synthetically and industrially important polymers is a long-standing demand in polymer chemistry, suffering from the lack of a general synthetic route, the proposed method offers a green, practical, and robust solution to this aim.
Keywords: RETARDANT POLYPHOSPHATE ESTERS; CLICK REACTIONS; CONDENSATION POLYMERS; FLAME RETARDANTS; PHOSPHORUS; POLY(PHOSPHOESTER)S; MONOMERS